2012
DOI: 10.1177/1934578x1200700323
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Sulfur Compounds in Plant Defence

Abstract: The multiplicity of chemical structures of sulfur containing compounds, influenced in part by the element's several oxidation states, directly results in diverse modes of action for sulfur-containing natural products synthesized as secondary metabolites in plants. Sulfur-containing natural products constitute a formidable wall of defence against a wide range of pathogens and pests. Steady progress in the development of new technologies have advanced research in this area, helping to uncover the role of such im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 75 publications
0
38
0
1
Order By: Relevance
“…Even so, when present, sulfur is often the key to biological activity of secondary metabolites. Important examples are the highly reactive glucosinolate‐derived isothiocyanates7, 8 and polysulfides that act as plant defense agents,9, 10 thiazole‐bearing cytotoxic compounds,11 and polythioamide pharmacophores in antibacterial Clostridium metabolites 12. 13 A structurally and functionally outstanding sulfur‐containing moiety is the transannular disulfide bridge in epidithiodiketopiperazines (ETP), a family of microbial toxins 14.…”
Section: Methodsmentioning
confidence: 99%
“…Even so, when present, sulfur is often the key to biological activity of secondary metabolites. Important examples are the highly reactive glucosinolate‐derived isothiocyanates7, 8 and polysulfides that act as plant defense agents,9, 10 thiazole‐bearing cytotoxic compounds,11 and polythioamide pharmacophores in antibacterial Clostridium metabolites 12. 13 A structurally and functionally outstanding sulfur‐containing moiety is the transannular disulfide bridge in epidithiodiketopiperazines (ETP), a family of microbial toxins 14.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfur compounds are considered as the main components in sweet F. assa-foetida. Sulfur-containing products constitute a formidable wall of defense against a wide range of pathogens and pests (Nwachukwu et al 2012). In addition, it has been shown that thiourea as the main sulfur component in sweet F. assa-foetida can act as a ROS scavenger and improve the antioxidant defense system in plants (Kelner et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…En las alcaparras se han encontrado compuestos volátiles como los isotiocianatos, glucosinolatos, triterpenoides, entre otros. Los beneficios médicos, farmacéuticos y nutricionales de los glucosinolatos e isotiocianatos están reconocidos en carcinogénesis, enfermedades cardiovasculares y neurológicas (Dinkova-kostova y Kostov 2012, Boddupalli et al, 2012, también forman parte de un potente mecanismo de defensa de la planta contra los patógenos (Nwachukwu et al, 2012). Brevard et al (1992) identificaron 160 componentes del sabor de las alcaparras encurtidas analizadas, incluyendo azufre elemental (S8) y más de 40 compuestos que contienen azufre, entre ellos tiocianatos e isotiocianatos.…”
Section: Composiciónunclassified